EVALUATION OF NEW TECHNOLOGIES FOR RAPID DIAGNOSTIC TESTING IN THE LABORATORY - Aqdi Ahmed Saleh Y, Abdullah Abdulrhman Ali Alasmari, Sumayyah Hassan Salman Almalki, Mohammed Mahdi Abdullah Al Jaran, Saleh Shuaib Alrashidi , Sattam Dhabel Alotaibi, Jaber Ahmed Ali Alsharah, ,; Hind Saad Alabdulsalam, Safiah Yahay Mohammed Muqri ,Salah Nasser Rashed Alfdhily, Eid Muhaysin Sarhan Alanazi, Fawaz Awad Zaben Alenazi ,Mohammed Ousi Asiri, Ali Ahmad Ali Alshadidi, (Chelonian Research Foundation, 2022)
Assessing novel technologies for expeditious diagnostic testing inside laboratory settings is of paramount importance in effectively tackling the urgent issues surrounding antibiotic misuse and antimicrobial resistance (AMR). The existing condition of medical facilities is characterized by a deficiency in a comprehensive and efficient diagnostic system capable of accurately identifying the etiological agent, distinguishing between viral and microbial illnesses, detecting antibiotic resistance, and providing guidance for suitable antimicrobial interventions. The primary objective of this research is to evaluate the progress made in diagnostic technologies and comprehend their possible implications in tackling these difficulties. This research investigates a range of technical developments in the field of quick diagnostic testing. These advancements include nucleic acid synthesis methods, electrochemical techniques, microarrays, micro- and nanoparticles, as well as mass spectrometry applications. These technological advancements possess the capacity to greatly enhance the efficiency and precision of infectious illness diagnosis, therefore empowering healthcare practitioners to make treatment choices based on empirical data and mitigate the abuse of antibiotics. Significant endeavors are now underway to augment antibacterial susceptibility and microbial detection methodologies. Conventional approaches, while efficient, may be laborious, sometimes requiring many days for outcomes. The research emphasizes the need for expeditious diagnostic tools that provide prompt and precise outcomes, especially in outpatient environments where such tests are often inaccessible. In summary, the assessment of novel technologies for expeditious diagnostic testing inside laboratory settings has encouraging prospects for tackling the obstacles presented by antibiotic misuse and AMR. The possibility for revolutionizing infectious disease treatment, reducing antibiotic abuse, and efficiently managing AMR exists with the implementation of these developments. Nevertheless, more investigation and regulatory authorizations are essential to guarantee the extensive use of these technologies in medical facilities around the globe. Keywords: rapid diagnostic testing, laboratory, antibiotic abuse, antimicrobial resistance, medical centers.